Octagonal toroid microcavity for mechanically robust optical coupling - Ryo Suzuki; Takumi Kato; Tomohiro Tetsumoto; Takasumi Tanabe (AIP Advances, 2015)
Light is usually coupled to a whispering gallery mode cavity using a tapered fiber. However, it is difficult to stabilize the optical coupling against mechanical vibration because it requires sub-μm control of the gap distance between the fiber and cavity. In this study, we experimentally demonstrate mechanically robust coupling that we realize by allowing the tapered fiber to touch the sidewall of the cavity. By using an octagonal toroid microcavity, we prevent the cavity-waveguide system from over coupling and achieve critical coupling even when the fiber is in contact with the surface of the cavity. We show by numerical analysis that such a deformed microcavity is required if we need to control the coupling, since a circular cavity usually overcouples when the fiber contacts the surface. The fabricated octagonal silica toroid microcavity exhibits a quality factor of 2.2 × 104 when the tapered fiber touches a cavity with a diameter of 80 μm.